Phytochemical and Pharmacological Properties of Vernonia amygdalina: A Review - Alara, Oluwaseun Ruth; Nour, A. H.; Siti Kholijah, Abdul Mudalip; Olalere, Olusegun Abayomi (Penerbit UMP, 2017)
Vernonia amygdalina has been a known food and medicinal plants used in Asia and Africa (West Africa) due to its pharmacological effects (antioxidant, anti-diabetes, anti-inflammatory, anticancer, anti-malaria, and among others). The phytochemical studies revealed that this plant is enriched with proteins, fats, fibres, amino acids, minerals, vitamins, and carbohydrates. Many bioactive compounds had been isolated from its extracts. Therefore, this review summarized the overview of the bioactive compounds, phytochemical and pharmacological properties of V. amygdalina as well as its mechanism of action and toxicology.